Honeycomb core material carbon fiber composite material and preparation method thereof

By spraying metal particles into the honeycomb core carbon fiber composite material and forming a thermosetting resin layer, combined with hot pressing process and ultrasonic filling technology, the problems of debonding and weight increase in the existing honeycomb core plates during the bonding process are solved, and a honeycomb core carbon fiber composite material with high bond strength and electromagnetic shielding performance are achieved.

CN119795679APending Publication Date: 2025-04-11JIANGSU AOSHENG COMPOSITE MATERIALS HI TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411980459.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the bonding process of existing honeycomb sandwich plates, honeycomb debonding due to curing thermal stress, etc., performance loss, and the structural adhesive film is heavy, which increases the overall weight and cannot meet the lightweight requirements.

Method used

The honeycomb core carbon fiber composite material is used to spray metal particles on the surface of the honeycomb material and form a thermoset resin layer on the carbon fiber material. Combined with hot pressing process and ultrasonic filling technology, the bonding strength between layers and electromagnetic shielding performance are enhanced.

Benefits of technology

It has achieved a carbon fiber composite material with light weight, high interlayer bonding strength and good electromagnetic shielding performance, avoiding honeycomb debonding, reducing overall weight, and broadening application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222340170000071
    Figure BDA0005222340170000071
  • Figure BDA0005222340170000081
    Figure BDA0005222340170000081
  • Figure BDA0005222340170000082
    Figure BDA0005222340170000082
Patent Text Reader

Abstract

The invention relates to a honeycomb core material carbon fiber composite material and a preparation method thereof, the honeycomb core material carbon fiber composite material comprises a honeycomb core material, an upper surface layer and a lower surface layer, the honeycomb core material comprises a honeycomb material and a filler, the surface of the honeycomb material is sprayed with metal particles, and the filler comprises thermosetting resin; the upper surface layer and / or the lower surface layer are / is a carbon fiber resin layer, and the carbon fiber resin layer comprises a carbon fiber material coated with thermosetting resin. The compound in-situ filling foaming agent is used for carrying out foaming on thermosetting resin, foaming pores of the thermosetting resin are developed and uniform, and the impact resistance of the composite board is improved; the foaming agent is foamed after in-situ filling, so that the volume of the thermosetting resin is expanded, the filler is further in contact with the carbon fiber resin layer, the interlayer cohesiveness is further improved, and the interlayer shear strength of the composite board is better; metal particles are arranged on the surface of the honeycomb-shaped material and coordinate with the filler, the honeycomb metal layer and the carbon fiber material to form electromagnetic shielding, and the application field of the composite board is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, in particular to a carbon fiber composite material, and specifically to a honeycomb core carbon fiber composite material and a preparation method thereof. Background Art

[0002] Honeycomb materials are bionic inventions that were invented after studying and analyzing the characteristics of natural honeycomb structures. Both facts and theories have proven that this structure achieves the largest space area with the least amount of material and has the best structural stability. Honeycomb materials have excellent compression and bending resistance and ultra-light structural characteristics. Compared with solid materials of the same type, honeycomb materials have the highest specific strength and specific stiffness among known materials.

[0003] Honeycomb structural panels have many superior properties. Compared with other structures, the closed hexagonal honeycomb structure can obtain the maximum load-bearing capacity with the least material. In actual use, people often add two layers of panels on both sides of the honeycomb core material, and the honeycomb core material and the panels are bonded with adhesive. However, most panel prepregs have poor adhesion to the honeycomb core material, and structural adhesive films are often required to complete the connection between the panel and the honeycomb. The panel prepreg resin and the structural adhesive film resin often cause debonding after curing due to differences in the degree of curing or mismatched components. Therefore, the panel must be cured in advance, and the panel and the honeycomb core material must be bonded together with adhesive films for secondary curing. However, the honeycomb debonding phenomenon often causes performance loss due to curing thermal stress, which poses a safety hazard and increases the maintenance burden. At the same time, the structural adhesive film usually has a large gram weight, which increases the overall weight of the honeycomb core structure, which is not conducive to the lightweight requirements of the components.

[0004] Refer to the patent with publication number CN105291524A, which discloses a honeycomb sandwich panel and its processing method, the honeycomb sandwich panel includes at least one layer of aramid honeycomb core and a strengthening layer, the strengthening layer has one more layer than the aramid honeycomb core, the surface of at least one side wall of the aramid honeycomb sandwich panel is a special-shaped surface, and a layer of the honeycomb core is sandwiched between every two adjacent strengthening layers to meet the requirements of occasions that require honeycomb materials of special shapes. However, it uses a film to achieve the composite between layers, and the overall weight of the material increases. In addition, the patent mainly focuses on the design of curved structures, lacks optimization of the mechanical properties, wave absorption properties and fatigue resistance of the material, and does not consider electromagnetic shielding, which reduces the application field of the material. Summary of the invention

[0005] An object of the present invention is to provide a honeycomb core material carbon fiber composite material, in particular a honeycomb core material carbon fiber composite material with light weight, high interlayer bonding strength and good electromagnetic shielding performance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A honeycomb core material carbon fiber composite material comprises a honeycomb core material, an upper surface layer, and a lower surface layer, wherein the honeycomb core material is located between the upper surface layer and the lower surface layer, the honeycomb core material comprises a honeycomb material and a filler, the surface of the honeycomb material is sprayed with metal particles, and the filler contains a thermosetting resin; the upper surface layer and / or the lower surface layer is a carbon fiber resin layer, and the carbon fiber resin layer comprises a carbon fiber material coated with a thermosetting resin.

[0008] Preferably, in the above technical solution, the stable compressive strength of the honeycomb material is 1 to 5 MPa, and the stable compressive strength is the maximum compressive stress that the sample withstands until it breaks or yields when the honeycomb resin is compressed perpendicular to the plane of the honeycomb holes, and the stable compressive strength is tested in accordance with ASTM C365-2011 standard.

[0009] Further preferably, considering better impact resistance, the stable compressive strength is 2-4 MPa.

[0010] Preferably, in the above technical solution, the transverse (W direction) and longitudinal (L direction) shear properties of the honeycomb material are 0.5-3 MPa, and the shear properties are tested according to ASTM C273-2007 standard.

[0011] Further preferably, considering the shear strength of the composite material, the shear properties of the honeycomb material in the W direction and the L direction are 1.5 to 3 MPa.

[0012] Preferably, in the above technical solution, the honeycomb core material is a low-density honeycomb material, and the honeycomb material is selected from one or more of honeycomb resin, glass cloth honeycomb, aluminum honeycomb, graphite honeycomb, paper honeycomb, stainless steel honeycomb, and cotton cloth honeycomb.

[0013] Further preferably, in consideration of moisture resistance, strength and lightness, the honeycomb material is preferably honeycomb resin.

[0014] Further preferably, the honeycomb resin is a honeycomb material formed by stacking polymer resin sheets, which has the characteristics of acid and alkali resistance and high strength, and the honeycomb resin is selected from one or more of aramid resin, polyvinyl chloride resin, polyester resin, polyamide resin, polyether resin, and polysulfone resin.

[0015] Further preferably, considering the mechanical strength, the honeycomb resin is preferably aramid resin.

[0016] In the above technical solution, preferably, the metal particles are selected from one or more of iron powder, cobalt powder, nickel powder, copper powder, zinc powder, aluminum powder, titanium powder, vanadium powder, chromium powder, manganese powder, silver powder, platinum powder, gold powder, iron oxide, nickel oxide, cobalt oxide, copper oxide, aluminum oxide, titanium oxide, and tungsten oxide. Spraying metal particles can increase the electromagnetic shielding performance of carbon fiber composites and broaden the application scope of composite panels.

[0017] Further preferably, considering the electromagnetic shielding effectiveness, the metal particles are preferably one or more of copper powder and copper oxide.

[0018] Further preferably, considering the simplicity of the spraying process, the metal particles are preferably one or more of titanium dioxide and aluminum oxide.

[0019] Preferably, in the above technical solution, the thickness of the carbon fiber resin layer is 0.5-2 mm, that is, the thickness of the upper surface layer and the lower surface layer is 0.5-2 mm, and the carbon fiber material is completely coated by the thermosetting resin.

[0020] Preferably, in the above technical solution, the thickness of the carbon fiber material is 0.05-1.00 mm, and the thickness is tested by a thickness gauge, and the thickness of 9 different places on the carbon fiber material is measured and the average value is taken as the thickness of the carbon fiber material.

[0021] Further preferably, considering factors such as strength requirements and cost, the thickness of the carbon fiber material is preferably 0.05 to 0.5 mm.

[0022] Preferably, in the above technical solution, the tensile strength of the carbon fiber material is greater than 3500 MPa, and the tensile strength is tested according to GB / T1040.1-2018. The thicker the material, the stronger its tensile strength.

[0023] Further preferably, considering factors such as strength requirements and cost, the tensile strength of the carbon fiber material is greater than 4000 MPa.

[0024] Preferably, in the above technical solution, the carbon fiber material is selected from carbon fiber paper, carbon fiber cloth, carbon fiber felt, and carbon fiber braid.

[0025] Further preferably, considering the overall mechanical properties of the composite plate material and a better construction process, the carbon fiber material is preferably carbon fiber cloth.

[0026] Preferably, in the above technical solution, the thermosetting resin is selected from one or more of thermosetting phenolic resin, thermosetting polyimide resin, thermosetting epoxy resin, thermosetting unsaturated polyester resin, thermosetting polyurethane resin, thermosetting urea-formaldehyde resin, thermosetting silicone resin and thermosetting melamine-formaldehyde resin.

[0027] Further preferably, the thermosetting resin in the filler expands under the action of the foaming agent, so that the filler can fully contact the honeycomb resin and the carbon fiber resin layer, thereby improving the bonding strength and increasing the shear strength between the composite layers. To ensure the excellent strength of the composite material, the thermosetting resin in the filler is preferably a thermosetting phenolic resin or a thermosetting polyimide resin.

[0028] Further preferably, for the thermosetting resin in the carbon fiber resin layer, considering the material cost and service life of the composite material, the thermosetting resin in the carbon fiber resin layer is preferably a thermosetting epoxy resin.

[0029] Another object of the present invention is to provide a method for preparing a honeycomb core material carbon fiber composite material.

[0030] In order to achieve the above object, the technical solution adopted by the present invention is:

[0031] A method for preparing a honeycomb core carbon fiber composite material, comprising:

[0032] (1) Prepare filler: Mix thermosetting resin, curing agent, foaming agent and carbon fiber to obtain filler, wherein:

[0033] Based on 100 parts by weight of thermosetting resin: 5 to 15 parts by weight of curing agent; 10 to 30 parts by weight of foaming agent; 5 to 15 parts by weight of carbon fiber;

[0034] Preparation of honeycomb metal layer: spraying metal particles onto honeycomb material to obtain honeycomb metal layer;

[0035] Preparation of the upper surface layer and the lower surface layer: connecting a wire to the carbon fiber material, placing the carbon fiber material connected with the wire in a thermosetting resin solution for dipping, and taking it out after curing to obtain a carbon fiber resin layer. Connecting the wire to the carbon fiber material is convenient for taking out the carbon fiber material from the thermosetting resin solution, and on the other hand, the wire can generate heat after being connected to electricity, thereby reducing the curing time;

[0036] (2) hot-pressing and bonding the honeycomb metal layer and the lower surface layer, injecting filler into the honeycomb holes of the metal honeycomb layer, and hot-pressing to obtain the honeycomb core material and the bonding layer of the lower surface layer;

[0037] (3) The upper surface layer, the honeycomb core material and the lower surface layer are hot pressed and cured to prepare a honeycomb core material carbon fiber composite board.

[0038] The above technical solution is preferably, considering the bubble temperature of the foaming agent and the hot pressing temperature of the hot pressing process, the Vicat softening point temperature of the thermosetting resin in the filler is 80-130°C, and the Vicat softening point temperature is the temperature at which the sample is placed in a liquid heat transfer medium under a certain load and a certain constant temperature rise condition. 2 The temperature when the indenter is pressed into a depth of 1 mm.

[0039] In the above technical solution, preferably, considering the curing time and the foaming efficiency of the foaming agent, the curing agent is aluminum dihydrogen phosphate powder curing agent, the curing agent can cause cross-linking between polymer molecules, and the aluminum dihydrogen phosphate powder curing agent can be evenly mixed with other components of the filler.

[0040] Preferably, in the above technical solution, the average particle size of the foaming agent is 10 to 100 nm.

[0041] Further preferably, considering the mixing uniformity of the foaming agent and the thermosetting resin, and the amount of foaming pores, the average particle size of the foaming agent is preferably 10 to 50 nm.

[0042] In the above technical solution, preferably, the foaming agent is selected from one or more of 2,2′-azobisisobutyronitrile, diisopropyl azodicarboxylate, barium azodicarboxylate, diethyl azodicarboxylate, azoaminobenzene, N,N′-dimethyl-N,N′-dinitrosoterephthalamide, benzenesulfonylhydrazide, p-toluenesulfonylhydrazide and carbohydrazide, and the foaming agent can make the thermosetting resin generate pores.

[0043] Further preferably, considering the convenience of processing, the chemical foaming agent decomposes after heating and can release a large amount of gas, thereby forming a compound with pores in the polymer composition; considering the temperature of the decomposition and release of gas and the curing temperature, the foaming agent is preferably one or more of carbohydrazide and benzenesulfonylhydrazide.

[0044] More preferably, considering the foaming time and the foaming rate, the foaming agent is 15 to 25 parts by weight.

[0045] Preferably, in the above technical solution, the carbon fiber is short carbon fiber with an average fiber length of 1 to 5 mm.

[0046] Further preferably, considering the cost and the strength of the composite material, the carbon fiber staple fibers are 8 to 12 parts by weight.

[0047] Further preferably, considering the cost and the strength of the composite material, the average fiber length of the carbon fiber is 1 to 3 mm.

[0048] Preferably, in the above technical solution, the metal particles are 20 to 30 parts by weight. If the amount of the metal particles is small, the electromagnetic shielding efficiency of the composite material is reduced. If the amount of the metal particles is large, it is easy to cause uneven dispersion of the metal particles and the thermosetting resin and increase the weight of the composite material.

[0049] Preferably, in the above technical solution, the average particle size of the metal particles is 10 to 100 nm.

[0050] Further preferably, considering the uniformity of the filler mixing, the average particle size of the metal particles is preferably 10 to 50 nm.

[0051] Preferably, in the above technical solution, the curing time is 5 to 10 minutes.

[0052] Preferably, in the above technical solution, the temperature of hot pressing bonding is 80-130° C., and the pressure is 0.1-1 MPa; and the filling and hot pressing are repeated 2-3 times.

[0053] Preferably, the above technical solution is heated to 80-130°C, kept for 1-3 hours, then pressurized to 2-3MPa, kept for 30-60 minutes, and cooled to room temperature to obtain a honeycomb core carbon fiber composite board.

[0054] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0055] The present invention selects a honeycomb material with certain impact resistance as a base material, and mixes a thermosetting resin with an in-situ filling foaming agent for a foaming process. The foamed pores of the thermosetting resin are developed and connected evenly, thereby improving the impact resistance of the composite board.

[0056] The present invention uses a foaming agent to foam after in-situ filling, expands the volume of the thermosetting resin, and allows the filler to further contact the carbon fiber resin layer. After the hot pressing process, the interlayer adhesion is further improved, and the interlayer shear strength of the composite board is better.

[0057] The honeycomb material of the present invention has metal particles on its surface, which coordinate with the filler, the honeycomb metal layer and the carbon fiber material to form electromagnetic shielding layer by layer, thus broadening the application field of the composite board. DETAILED DESCRIPTION

[0058] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] The raw materials used in each embodiment and comparative example are as follows:

[0060]

Honeycomb resin

[0061] A1: Aramid honeycomb resin, ACCH-1-2.75-80 aramid honeycomb resin produced by AVIC Composite Materials Co., Ltd., with a stable plane compression strength of 4.74MPa, L-direction shear performance of 2.51MPa, and W-direction shear performance of 1.58MPa.

[0062] A2: Aramid honeycomb resin, ACCH-1-2.83-64 aramid honeycomb resin produced by AVIC Composite Materials Co., Ltd., with a stable plane compression strength of 2.44MPa, L-direction shear performance of 1.81MPa, and W-direction shear performance of 1.05MPa.

[0063]

Metal particles

[0064] B1: Nano titanium dioxide, XFI63 nano titanium dioxide produced by Pioneer Nano Corporation.

[0065] B2: Nano alumina, XFI08 nano alumina produced by Pioneer Nano Corporation.

[0066]

Thermosetting resin

[0067] C1: Thermosetting polyurethane resin, A1105 polyurethane resin produced by Asahikawa Chemical (Suzhou) Co., Ltd., Vicat softening point 100°C.

[0068] C2: Thermosetting phenolic resin, 2123 phenolic resin produced by Wuxi Xinyehao Chemical Co., Ltd., Vicat softening point 120℃.

[0069]

Curing agent

[0070] D: Aluminum dihydrogen phosphate, 236-875-2 curing agent produced by Zhengzhou Yucai Phosphate Chemical Plant.

[0071]

Foaming agent

[0072] E1: Benzenesulfonylhydrazide, McLean reagent B802456 benzenesulfonylhydrazide foaming agent, average particle size is 15-30nm.

[0073] E2: Carbohydrazide, McLean reagent produced C833291 carbohydrazide foaming agent, with an average particle size of 15-30nm.

[0074]

Carbon fiber staple

[0075] F1: Carbon fiber staple fiber, T800H chopped carbon fiber produced by Toray Industries, Ltd., Japan, fiber length 1mm.

[0076] F2: Carbon fiber staple fiber, T800H chopped carbon fiber produced by Toray Industries, Ltd., Japan, fiber length 4mm.

[0077]

Metal compounds

[0078] G1: Copper powder, DK-Cu-001 nano copper powder produced by Beijing Dekedaojin Technology Co., Ltd., with an average particle size of 50nm.

[0079] G2: Copper oxide powder, DK-CuO-001 nano copper oxide powder produced by Beijing Dekedaojin Technology Co., Ltd., with an average particle size of 40nm.

[0080] The fillers (M1 to M16) were prepared according to the formula shown in Table 1 by weighing and stirring evenly at room temperature.

[0081] Table 1:

[0082]

[0083]

[0084]

Carbon Fiber Cloth

[0085] H1: Carbon fiber cloth, H1K-CT120 carbon fiber cloth produced by Huaheng High Performance Fiber Weaving Co., Ltd., with a thickness of 0.16mm. H2: Carbon fiber cloth, H1K-CT320 carbon fiber cloth produced by Huaheng High Performance Fiber Weaving Co., Ltd., with a thickness of 0.42mm.

[0086]

Thermosetting epoxy resin

[0087] N: Thermosetting epoxy resin, EPICLON4050 bisphenol A epoxy resin produced by Dainippon Ink Co., Ltd.

[0088] The carbon fiber composite plates of Examples 1 to 16 and Comparative Examples 1 to 3 are prepared according to the formula shown in Table 2:

[0089] Table 2:

[0090]

[0091]

[0092] Examples 1 to 16 and Comparative Examples 1 to 3 were prepared by the following steps:

[0093] S1: Using plasma spraying process, using plasma as heat source, the metal particles are heated and atomized and then sprayed onto the surface of honeycomb resin to obtain a honeycomb metal layer;

[0094] S2: preparing an upper surface layer and a lower surface layer, connecting a conductor to the carbon fiber cloth, immersing the carbon fiber cloth connected with the conductor in an epoxy resin solution for 30 to 60 minutes, and taking out after micro-curing to obtain a carbon fiber resin layer and an upper surface layer and a lower surface layer;

[0095] S3: hot-pressing the lower surface layer and the honeycomb metal layer, then injecting the filler into the honeycomb holes, ultrasonically hot-pressing (temperature 80-130°C, pressure 0.1-1MPa, time 3-10min), repeating the ultrasonic hot-pressing process 2-3 times to obtain a bonding layer of the honeycomb metal layer and the lower surface layer;

[0096] S4: The composite material of the upper surface layer, the honeycomb core material and the lower surface layer is heated to 80-130°C, kept for 1-3 hours, then pressurized to 2-3MPa, kept for 30-60 minutes, and then cooled to obtain a carbon fiber composite plate.

[0097] Comparative Example 4 was prepared according to the following steps:

[0098] S1: Using plasma spraying process, using plasma as heat source, the metal particles are heated and atomized and then sprayed onto the surface of honeycomb resin to obtain a honeycomb metal layer;

[0099] S2: preparing an upper surface layer and a lower surface layer, connecting a conductor to the carbon fiber cloth, immersing the carbon fiber cloth connected with the conductor in an epoxy resin solution for 30 to 60 minutes, and taking out after micro-curing to obtain a carbon fiber resin layer and an upper surface layer and a lower surface layer;

[0100] S3: The composite material of the upper surface layer, the honeycomb core material and the lower surface layer is heated to 80-130°C, kept for 1-3 hours, then pressurized to 2-3MPa, kept for 30-60 minutes, and then cooled to obtain a carbon fiber composite plate.

[0101] Comparative Example 5 was prepared according to the following steps:

[0102] S1: preparing an upper surface layer and a lower surface layer, connecting a conductor to the carbon fiber cloth, immersing the carbon fiber cloth connected with the conductor in an epoxy resin solution for 30 to 60 minutes, and taking out after micro-curing to obtain a carbon fiber resin layer and an upper surface layer and a lower surface layer;

[0103] S2: hot-pressing the lower surface layer and the honeycomb metal layer, then injecting the filler into the honeycomb holes, ultrasonically hot-pressing (temperature 80-130°C, pressure 0.1-1MPa, time 3-10min), repeating the ultrasonic hot-pressing process 2-3 times to obtain a bonding layer of the honeycomb metal layer and the lower surface layer;

[0104] S3: The composite material of the upper surface layer, the honeycomb core material and the lower surface layer is heated to 80-130°C, kept for 1-3 hours, then pressurized to 2-3MPa, kept for 30-60 minutes, and then cooled to obtain a carbon fiber composite plate.

[0105] The following tests were conducted on the carbon fiber composite panels. Unless otherwise specified, all tests were conducted at 25°C. The main indicators are as follows:

[0106] 1. Destructive impact strength: refer to ASTM D7136-2007. Use Instron 9350 fully automatic drop hammer impact tester for testing, the total weight of the drop hammer is 1 ± 0.05 kg, and the diameter of the impact head is 3 ± 0.1 mm. Each group of samples starts the test with a kinetic energy of 100 J, and a gradient of 10 J until the sample is destroyed to obtain the destructive impact strength of the sample.

[0107] 2. Tensile strength: Tested according to GB / T1040.1-2018, the specimen is stretched at a rate of 5 mm / min, and the specimen size is 100 mm × 10 mm;

[0108] 3. Interlaminar shear failure stress: Tested according to the test method of GB / T28889-2012, stretching the specimen at a rate of 5 mm / min.

[0109] 4. Average electromagnetic shielding effectiveness: tested in accordance with GB / T30142-2013 standard, the test frequency range is 8~12GHz.

[0110] Table 3:

[0111]

[0112] As shown in Tables 2 and 3, compared with the comparative example, the carbon fiber composite plate prepared in the embodiment has better impact resistance, stronger interlaminar shear stress, and better electromagnetic shielding effectiveness; the carbon fiber composite plate prepared in the embodiment takes into account both mechanical properties and electromagnetic shielding effectiveness, and has a wide range of applications.

[0113] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A honeycomb core carbon fiber composite material, comprising a honeycomb core, an upper surface layer, and a lower surface layer, wherein the honeycomb core is located between the upper surface layer and the lower surface layer, and characterized in that: The honeycomb core material comprises a honeycomb material and a filler, the surface of the honeycomb material is sprayed with metal particles, and the filler comprises a thermosetting resin; The upper surface layer and / or the lower surface layer is a carbon fiber resin layer, and the carbon fiber resin layer includes a carbon fiber material coated with a thermosetting resin.

2. The honeycomb core carbon fiber composite material according to claim 1, characterized in that: The stable compressive strength of the honeycomb material is 1 to 5 MPa; The transverse and longitudinal shear properties of the honeycomb material are 0.5-3MPa.

3. The honeycomb core carbon fiber composite material according to claim 1 or 2, characterized in that: The honeycomb material is selected from one or more of honeycomb resin, glass cloth honeycomb, aluminum honeycomb, graphite honeycomb, paper honeycomb, stainless steel honeycomb and cotton cloth honeycomb.

4. The honeycomb core carbon fiber composite material according to claim 3, characterized in that: The honeycomb material is a honeycomb resin, and the honeycomb resin is selected from one or more of aramid resin, polyvinyl chloride resin, polyester resin, polyamide resin, polyether resin, and polysulfone resin.

5. The honeycomb core carbon fiber composite material according to claim 1, characterized in that: The metal particles are selected from one or more of iron powder, cobalt powder, nickel powder, copper powder, zinc powder, aluminum powder, titanium powder, vanadium powder, chromium powder, manganese powder, silver powder, platinum powder, gold powder, iron oxide, nickel oxide, cobalt oxide, copper oxide, aluminum oxide, titanium oxide, and tungsten oxide.

6. The honeycomb core material carbon fiber composite material according to claim 1, characterized in that: The thickness of the carbon fiber resin layer is 0.5 to 2 mm; The carbon fiber material is completely coated by the thermosetting resin; The thickness of the carbon fiber material is 0.05-1.00 mm; The tensile strength of the carbon fiber material is greater than 3500 MPa.

7. The honeycomb core carbon fiber composite material according to claim 1, characterized in that: The carbon fiber material is selected from carbon fiber paper, carbon fiber cloth, carbon fiber felt, and carbon fiber braid.

8. The honeycomb core carbon fiber composite material according to claim 1, characterized in that: The thermosetting resin is selected from one or more of thermosetting phenolic resin, thermosetting polyimide resin, thermosetting epoxy resin, thermosetting unsaturated polyester resin, thermosetting polyurethane resin, thermosetting urea-formaldehyde resin, thermosetting silicone resin and thermosetting melamine-formaldehyde resin.

9. A method for preparing the honeycomb core carbon fiber composite material according to any one of claims 1 to 9, characterized in that: include: (1) Prepare filler: Mix thermosetting resin, curing agent, foaming agent and carbon fiber to obtain filler, wherein: Based on 100 parts by weight of thermosetting resin: 5 to 15 parts by weight of curing agent; 10 to 30 parts by weight of foaming agent; 5 to 15 parts by weight of carbon fiber; Preparation of honeycomb metal layer: spraying metal particles onto honeycomb material to obtain honeycomb metal layer; Preparing the upper surface layer and the lower surface layer: connecting a wire to the carbon fiber material, placing the carbon fiber material connected with the wire in a thermosetting resin solution for dipping, and taking it out after curing to obtain a carbon fiber resin layer; (2) hot-pressing and bonding the honeycomb metal layer and the lower surface layer, injecting filler into the honeycomb holes of the metal honeycomb layer, and hot-pressing to obtain the honeycomb core material and the bonding layer of the lower surface layer; (3) The upper surface layer, the honeycomb core material and the lower surface layer are hot pressed and cured to prepare a honeycomb core material carbon fiber composite board.

10. The method according to claim 9, characterized in that: In (1): the Vicat softening point temperature of the thermosetting resin is 80 to 130° C.; The curing agent is aluminum dihydrogen phosphate powder curing agent; The average particle size of the foaming agent is 10 to 100 nm; the foaming agent is selected from one or more of 2,2′-azobisisobutyronitrile, diisopropyl azodicarboxylate, barium azodicarboxylate, diethyl azodicarboxylate, azoaminobenzene, N,N′-dimethyl-N,N′-dinitrosoterephthalamide, benzenesulfonylhydrazide, p-toluenesulfonylhydrazide and carbohydrazide; The carbon fiber is short carbon fiber with an average fiber length of 1 to 5 mm; The average particle size of the metal particles is 10 to 100 nm; The curing time is 5 to 10 minutes; In (2): the temperature of hot pressing bonding is 80 to 130° C. and the pressure is 0.1 to 1 MPa; the filling and hot pressing are repeated 2 to 3 times; In (3): heating to 80-130° C., holding for 1-3 hours, then pressurizing to 2-3 MPa, holding for 30-60 minutes, and cooling to room temperature to obtain a honeycomb core carbon fiber composite board.

Citation Information

Patent Citations

  • Flame-retardant lightweight structure core and preparation method thereof

    CN105437683A

  • PP (polypropylene) honeycomb sandwich composite board and preparation method thereof

    CN108248124A

  • Lightweight square cabinet wall plate with wide frequency shielding function, and preparation method thereof

    CN108274830A

  • Carbon fiber aramid fiber honeycomb composite board as well as preparation process and application thereof

    CN117922112A